Teaching Writing Recount Text by Using Powtoon Video - Nuri Ati Ningsih (English Teaching Journal : A Journal of English Literature, Language and Education, 2021)
Powtoon. video and finding the advantages of using it. This research was a qualitative descriptive method.  It was done in class IX of SMPN 6 Madiun. The sample of this research is class IX H. The data were collected by doing observation, interview, and documentation. Then, it was analyzed through three techniques. They involve data reduction. Displaying data, conclusion and verification. The result of reserach shows that using Powtoon. Powtoon video in teaching writing recount text done in three-phase technique. It involves pre activities, main activities and post activities. The process of writing done based on Linses’ theory. Those are pre writing, writing, revising, editing and publishing. Powtoon video was played twice. First, it was played in pre activities to stimulate the students' understanding of the material. Second, it was used in main activities specifically in revising step to make sure the students about their works. The advantages of using Powtoon video in writing class are; (1) creating a joyful class; (2) raising the students’ motivation and enthusiasm in writing; (3) realize the students to be independent learners; and (4) develop the teachers’ creativity.